2020
DOI: 10.1016/j.cub.2020.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Cell Division: Interkinetic Nuclear… Mechanics

Abstract: New work reveals that interkinetic nuclear migration -the movement of nuclei towards the apical surface of dividing epithelial cells -is mechanically regulated, relying on a balance of forces between the mitotic cell and the surrounding tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In pseudostratified epithelia, nuclei must migrate to the apical surface to undergo mitosis. The mechanistic basis of this requirement is unclear, 17,20,29 but it is considered to be an essential feature of cell-cycle progression in pseudostratified epithelia (assumption A1). In accordance with previous findings, 21,22,25,[30][31][32] we assume that the apical-ward movement of G2 nuclei is an active process, probably driven by actomyosin.…”
Section: Modeling Interkinetic Nuclear Migrationmentioning
confidence: 99%
“…In pseudostratified epithelia, nuclei must migrate to the apical surface to undergo mitosis. The mechanistic basis of this requirement is unclear, 17,20,29 but it is considered to be an essential feature of cell-cycle progression in pseudostratified epithelia (assumption A1). In accordance with previous findings, 21,22,25,[30][31][32] we assume that the apical-ward movement of G2 nuclei is an active process, probably driven by actomyosin.…”
Section: Modeling Interkinetic Nuclear Migrationmentioning
confidence: 99%
“…IKNM are characteristic of many epithelia (46)(47)(48), hence our conclusions might be relevant to other tissues besides the neural tube. Our analysis indicated that IKNMs exert their effect on cell rearrangements by affecting the apical surface area kinetics of cells.…”
Section: Discussionmentioning
confidence: 79%